Industrial biotechnology of vitamins, biopigments, and antioxidants - Vandamme, Erick J., 1943-; Revuelta, Jos e Luis. (Weinheim, Germany : Wiley-VCH, 2016)
Vitamins are a group of physiologically very important, chemically quite complex organic compounds, that are essential for humans and animals. Some vitamins and other growth factors behave as antioxidants, while some can be considered as biopigments. As their chemical synthesis is laborious, their biotechnology-based synthesis and production via microbial fermentation has gained substantial interest within the last decades. Recent progress in microbial genetics and in metabolic engineering and implementation of innovative bioprocess technology has led to a biotechnology-based industrial production of many vitamins and related compounds. Divided into three sections, this volume covers: 1. water-soluble vitamins 2. fat-soluble vitamin compounds and 3. other growth factors, biopigments, and antioxidants. They are all reviewed systematically: from natural occurrence and assays, via biosynthesis, strain development, to industrially-employed biotechnological syntheses and applications.
Vitamins, Biopigments, Antioxidants and Related Compounds: A Historical, Physiological and (Bio)technological Perspective / Erick J Vandamme, Jos e L Revuelta -- Water-Soluble Vitamins. Industrial Production of Vitamin B by Microbial Fermentation / Jos e L Revuelta, Rodrigo Ledesma-Amaro, Alberto Jim enez -- Vitamin B, Niacin / Tek Chand Bhalla, Savitri -- Pantothenic Acid / Jesus Gonzalez-Lopez, Luis Aliaga, Alejandro Gonzalez-Martinez, Maria V Martinez-Toledo -- Folate: Relevance of Chemical and Microbial Production / Maddalena Rossi, Stefano Raimondi, Luca Costantino, Alberto Amaretti -- Water-Soluble Vitamins. Vitamin B -- Physiology, Production and Application / Janice Marie Sych, Christophe Lacroix, Marc JA Stevens -- Industrial Fermentation of Vitamin C / Weichao Yang, Hui Xu -- Direct Microbial Routes to Vitamin C Production / G unter Pappenberger, Hans-Peter Hohmann -- Fat Soluble Vitamins. Synthesis of -Carotene and Other Important Carotenoids with Bacteria / Christoph Albermann, Holger Beuttler -- [beta]-Carotene and Other Carotenoids and Pigments from Microalgae / Borhane Samir Grama, Antoine Delhaye, Spiros N Agathos, Clayton Jeffryes -- Microbial Production of Vitamin F and Other Polyunsaturated Fatty Acids / Colin Ratledge -- Vitamin Q: Property, Production and Application / Joong K Kim, Eun J Kim, Hyun Y Jung -- Pyrroloquinoline Quinone (PQQ) / Hirohide Toyama -- Other Growth Factors, Biopigments and Antioxidants. L-Carnitine, the Vitamin B: Uses and Production by the Secondary Metabolism of Bacteria / Vicente Bernal, Paula Arense, Manuel C anovas -- Application of Carnosine and Its Functionalised Derivatives / Isabelle Chevalot, Elmira Arab-Tehrany, Edouard Husson, Christine Gerardin -- Metabolism and Biotechnological Production of Gamma-Aminobutyric Acid (GABA) / Feng Shi, Yalan Ni, Nannan Wang -- Flavonoids: Functions, Metabolism and Biotechnology / Celestino Santos-Buelga, Ana M Gonz alez-Param as -- Pigments / Yanli Feng, Yanchun Shao, Youxiang Zhou, Wanping Chen, Fusheng Chen.
Includes bibliographical references and index.
Print version record.
Keywords: Vitamins -- Biotechnology; Pigments (Biology) -- Biotechnology; Antioxidants -- Biotechnology; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Electronic books